Pelatihan Aplikasi Mendelay Reference Manager Bagi Mahasiswa STEBI Badri Masduqi - Eka Diana; Khoirun Nisa; Tina Novi Lestari; Moh. Rofiki; Fatimatus Zahro; Khotimatul Husna (BADAN PENERBIT STIEPARI PRESS, 2023)
The citation system and compilation of the bibliography are two very important elements in the assessment used in journal accreditation. Journal managers, both national and international, enforce the use of Mendeley Reference Manager tools in preparing articles written by an author. Based on observations made, most students still use manual citations and a few also understand the use of Mendeley Desktop and do not understand the transition from the Mendeley Desktop application to the Mendeley Reference Manager. This service method is carried out with lectures, discussions and mentoring with several stages, namely the observation stage, the planning stage, the implementation stage, the mentoring stage and hold evaluation. The results of this service based on the pre-test conducted on training participants prior to the implementation of the training showed that most of the participants did not know and understand the operation of the Mendeley Reference Manager which is the latest version of the Mendeley application. The results of the post-training post test conducted on the participants showed a significant change after the Mendeley Reference Manager training.